2012
DOI: 10.1371/journal.pone.0030114
|View full text |Cite
|
Sign up to set email alerts
|

F420H2-Dependent Degradation of Aflatoxin and other Furanocoumarins Is Widespread throughout the Actinomycetales

Abstract: Two classes of F 420 -dependent reductases (FDR-A and FDR-B) that can reduce aflatoxins and thereby degrade them have previously been isolated from Mycobacterium smegmatis . One class, the FDR-A enzymes, has up to 100 times more activity than the other. F 420 is a cofactor with a low reduction potential that is largely confined to the Actinomycetales and some Archaea and Proteobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 45 publications
5
71
0
1
Order By: Relevance
“…Bacteria likewise appear to tightly couple substrate oxidation (glucose-6-phosphate and NADPH) to F 420 reduction, presumably to en- hance catalytic efficiency (Table 1). Partly due to its low redox potential, the F 420 H 2 produced is capable of reducing a wide range of organic compounds otherwise recalcitrant to activation as discussed in section 4 (28,54,55). Recent work also indicates that F 420 may be utilized in aerobic bacteria in hypoxic and anoxic environments, potentially substituting for high-potential nicotinamide cofactors (NAD and NADP) (Ϫ320 mV) (30,32,56).…”
Section: Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Bacteria likewise appear to tightly couple substrate oxidation (glucose-6-phosphate and NADPH) to F 420 reduction, presumably to en- hance catalytic efficiency (Table 1). Partly due to its low redox potential, the F 420 H 2 produced is capable of reducing a wide range of organic compounds otherwise recalcitrant to activation as discussed in section 4 (28,54,55). Recent work also indicates that F 420 may be utilized in aerobic bacteria in hypoxic and anoxic environments, potentially substituting for high-potential nicotinamide cofactors (NAD and NADP) (Ϫ320 mV) (30,32,56).…”
Section: Propertiesmentioning
confidence: 99%
“…There is also evidence that mycobacteria instead use electrons liberated from G6P by Fgd to directly detoxify exogenous agents (363). Two independent studies have demonstrated that FDOR-As rapidly reduce menadione and plumbagin using F 420 H 2 (30,32), and it is also plausible that these highly promiscuous proteins (28,55) can directly detoxify certain antibiotics too. However, genetic studies have yet to definitively link FDORs to antibiotic resistance and oxidative stress responses.…”
Section: Mycobacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Among them are the one-carbon reactions of methanogenesis (Thauer, 1998;Shima et al, 2000;Hagemeier et al, 2003), the biosynthesis pathways of tetracycline antibiotics (Wang et al, 2013) and the biodegradation of picrate and aflatoxins (Ebert et al, 2001;Taylor et al, 2010;Lapalikar et al, 2012). The cofactor appears to have been selected for these roles because of its unique electrochemical properties compared with the ubiquitous flavin and nicotinamide cofactors FMN (flavin mononucleotide), FAD (flavin adenine dinucleotide) and NAD(P) (nicotinamide adenine dinucleotide (phosphate)) (Walsh, 1986;Greening et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%